Enhancing Procurement Efficiency in South Africa through e-Reverse Auction Systems - Achieng, Mourine S; Ogundaini, Oluwamayowa O.; Mlitwa, Nhlanhla (Universitas Bina Darma, 2024)
The application of advanced technologies such as real-time trend analysis, business intelligence and procurement systems enhance business processes by facilitating informed decision making, driving digital transformation, and fostering growth. However, there remains a limited empirical understanding of the adoption and impact of electronic reverse auctions (eRA) systems in South African business sectors. The study aimed to identify how using eRA systems can improve procurement processes in South African business. A qualitative methodology was adopted to investigate the aim of the study. Data was collected using semi-structured interviews with 18 participants who were purposively sampled. The findings show that the primary benefits of eRA system usage include enhanced competitiveness, cost efficiency, transparency and strengthen buyer-seller relationships. Key outcomes for these benefits include increased supplier participation, lower procurement costs, a clear and open bidding process, and better communication between buyers and sellers. This study’s contribution is that, when used cautiously with identified risks eRA systems can streamline, standardize, and regulate procurement practices in South Africa’s business sectors. Drawing on the DeLone and McLean Information System Success Model, this paper highlights the dimensions by which eRA systems used in procurement processes can be evaluated to better understand and leverage their benefits within business.